Ventilator Associated Pneumonia: Continuous Versus Intermittent Administration of Piperacillin-Tazobactam in Intensive Care Unit Of - Sawarkar, Dr. Mahendra M.; Sawarkar, Dr. Shushrut Mahendra (International Journal of Innovative Research in Medical Science, 2018)
Introduction: Ventilator-associated pneumonia (VAP) can be defined as pneumonia occuring 48-72 hours or thereafter following endotracheal intubation, it is characterized by the presence of a new or progressive infiltrate, signs of systemic infection like fever, altered white blood cell count, changes in sputum characteristics. Duration of mechanical ventilation determines the type of organism that causes VAP. Early VAP is caused by pathogens that are sensitive to most of the antibiotics, whereas late onset VAP may be caused by multi-drug resistant bacteria. There is no gold standard diagnostic criterion for VAP. Many clinical methods have been recommended but there is no sensitivity or specificity to identify this disease. In this study we tried to compare the clinical outcomes of continuous and intermittent administration of Piperacillin-tazobactam. Material and Methods: For diagnosis of VAP following criteria were considered: white blood cell count more than10,000 cells/mm 3 or less than 4000 cells/ mm 3 ; new onset of purulent sputum or a change in sputum character; body temperature >38°C or <35.5°; chest X ray showing new or progressive infiltrate and a significant quantitative pathogen culture from respiratory secretions (tracheal aspirate >106 colony-forming units/ml or growth of ≥104 colony-forming units/mL of microorganism on bronchoscopic bronchoalveolar lavage (BAL) culture or isolation of the same microorganism in blood and respiratory secretions on third day and eighth day. APACHE II score were recorded on admission and CPIS was measured at the onset of VAP symptoms and at third and eighth day. Demographic and other variable of the patients were recorded. Results: 50 patients were included in the study of which 25 were placed in continuous Infusion (CI) group and 25 in intermittent infusion (II) group. APACHE II score on admission in CI and II was 19. 9 ± 4.9 and 21.4 ± 5.6 respectively. Duration of mechanical ventilation in CI group was 39.1 ± 20.5 days. Total number of antibiotics administered in CI group was 5.5 ± 2.0 and II group was 5 ± 1.5. Duration of piperacillin – tazobactum treatment was 21 ± 11.6 (days) in CI group and 19 ± 9.6 in II group. Mortality rate observed in CI was 8 (32%) and in II was 9 (36%). No significant difference was observed in CPIS scores of both the group in Day 1, day 3 and day 8. Conclusion: There is significant morbidity in critically ill patients with VAP and there is lack of gold standard criteria for diagnosis. No significant difference was observed in CI and II group in term of clinical outcome.